Food choice motives, attitude towards and intention to adopt personalised nutrition - Rankin, A (2018)
Objective: The present study explored associations between food choice motives, attitudes towards and intention to adopt personalised nutrition, to inform communication strategies based on consumer priorities and concerns. Design/Setting: A survey was administered online which included the Food Choice Questionnaire (FCQ) and items assessing attitudes towards and intention to adopt personalised nutrition. Subjects: Nationally representative samples were recruited in nine EU countries (n 9381). Results: Structural equation modelling indicated that the food choice motives weight control, mood, health and ethical concern had a positive association and price had a negative association with attitude towards, and intention to adopt, personalised nutrition. Health was positively associated and familiarity negatively associated with attitude towards personalised nutrition. The effects of weight control, ethical concern, mood and price on intention to adopt personalised nutrition were partially mediated by attitude. The effects of health and familiarity were fully mediated by attitude. Sensory appeal was negatively and directly associated with intention to adopt personalised nutrition. Conclusions: Personalised nutrition providers may benefit from taking into consideration the importance of underlying determinants of food choice in potential users, particularly weight control, mood and price, when promoting services and in tailoring communications that are motivationally relevant. Copyright (c) The Authors 2018